Handling Children in Conflict with the Law in Narcotics Crime Cases at the Aceh Tenggara Police Resort - Agung Ciptasari Panjaitan; Lidya Rahmadhani Hasibuan; Suci Ramadani (Judge : Jurnal Hukum, 2026)
This study aims to analyze the legal framework and the implementation of handling children in conflict with the law in narcotics crime cases at the Aceh Tenggara Police Resort, including the obstacles encountered in its implementation. The focus of this research lies in examining how applicable legal provisions are applied in practice and to what extent the protection of children can be optimally realized. The research method employed is empirical legal research with a juridical-empirical approach. Data were obtained through interviews with police officers at the Aceh Tenggara Police Resort as primary data, as well as literature studies covering statutory regulations and scientific literature as secondary data. All data were analyzed qualitatively to obtain a comprehensive understanding of the practice of handling juvenile cases. The results of the study indicate that, normatively, the handling of children has been regulated under Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, which emphasizes the principles of restorative justice, diversion, and the protection of the best interests of the child. In addition, Law Number 35 of 2009 concerning Narcotics also stipulates the importance of medical and social rehabilitation for drug abusers, including children. In practice, the Aceh Tenggara Police Resort has made efforts to implement these approaches. However, its implementation has not yet been optimal due to several obstacles, such as difficulties in reaching agreements in the diversion process, limited rehabilitation facilities, and a lack of public understanding of the concept of restorative justice. Therefore, it is necessary to enhance the capacity of law enforcement officers, strengthen supporting institutions, and increase public awareness to support the effectiveness of a juvenile criminal justice system that is oriented toward the protection and recovery of children.